2018
DOI: 10.1089/lap.2018.0147
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Pelvic Exenteration for Locally Advanced Rectal Cancer, Technique and Short-Term Outcomes

Abstract: Minimally invasive approaches can be used safely for total pelvic exenteration in locally advanced lower rectal adenocarcinoma. All patients had fast recovery with less blood loss. In all patients R0 resection was achieved with adequate margins. Long-term oncological outcomes are still uncertain and will require further follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…In case of bleeding, we would increase abdominal gas pressure, pack with tape gauze, and suture during perineal part of surgery. In our study, blood loss was 1000 mL (range 300-2000 mL), mean duration of surgery was 9.13 h (range 7-13 h), and mean postoperative stay was 14.6 days (range 9-25 days) [38] . When compared to other studies, we have demonstrated good perioperative outcomes [ Table 1].…”
Section: Ogura Et Almentioning
confidence: 55%
See 1 more Smart Citation
“…In case of bleeding, we would increase abdominal gas pressure, pack with tape gauze, and suture during perineal part of surgery. In our study, blood loss was 1000 mL (range 300-2000 mL), mean duration of surgery was 9.13 h (range 7-13 h), and mean postoperative stay was 14.6 days (range 9-25 days) [38] . When compared to other studies, we have demonstrated good perioperative outcomes [ Table 1].…”
Section: Ogura Et Almentioning
confidence: 55%
“…We standardized our technique of laparoscopic pelvic exenteration [37,38] . We use standard five-port technique followed by medialto-lateral retroperitoneal dissection, inferior mesenteric artery division, dissection of retrorectal space up to origin of levator ani, pararectal space dissection after medializing ureters, dissection of paravesical space to the level of the endopelvic fascia, dissection of Retzius space, division of dorsal vein complex, urethral transection, division of ureters, sigmoid transection, perineal dissection, and Bricker's ileal conduit through small infraumbilical incision.…”
Section: Ogura Et Almentioning
confidence: 99%
“…9 The dorsal venous complex is divided at the last stage of the pelvic dissection and in case there is any inadvertent bleeding, the intra-abdominal pneumo-peritoneum pressure is increased, the area packed with tape gauze and the bleeding vessel sutured during the perineal portion of the surgery. 9,15 The mean operative time was significantly longer in the MIS group when compared to the OPE group, but this was still lesser time when compared to other reports (Table 4). 5,21 The longer duration of MIS could be due to multiple factors such as the learning curve as our reports included all initial cases of MIS, the fact that surgical trainees as residents and fellows would perform the initial part of surgery and because of the extra time taken for intracorporeal urinary conduit, more number of LPLNDs and plastic reconstruction.…”
Section: Discussionmentioning
confidence: 64%
“… 10 We regularly perform exenterative surgeries, extended resections and multivisceral resections for CRC cases. 11 13 Our initial experience with regard to laparoscopic exenteration 14 15 and the techniques of robotic exenteration 16 18 were published previously. 9 There were only a few studies, which had compared MIS with open PE (OPE).…”
Section: Introductionmentioning
confidence: 99%
“…8 Also, laparoscopic resection for beyond and extended total mesorectal excision is performed with good short-term outcomes. 9,10 Owing to complete lockdown, when there is a shortage of blood supply, laparoscopic surgery will be advantageous as it gives minimal blood loss, decreased ward stay, and minimum intervention by staff for dressing and monitoring.…”
Section: Discussionmentioning
confidence: 99%